PENGARUH STRUKTUR AKTIVA, PERTUMBUHAN PENJUALAN DAN PROFITABILITAS TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PEMBIAYAAN YANG TERDAFTAR DI BEI 2019 - 2022 - Afifah, Dewi; Hamdun, Edy Kusnadi; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Organizations that provide capital or financial goods to conduct financial activities are known as financing institutions. The operational activities of this financing institution can be in the form of providing capital products or funds by not taking money directly from the general public in the form of savings, current accounts, deposits and promissory notes. This study aims to determine the effect of Asset Structure, Sales Growth and Profitability on Share Price with Capital Structure as an Intervening Variable in Financing Companies Listed on the IDX 2019 - 2022. This research method uses quantitative methods Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The result of direct influence hypothesis test using Smart PLS 3.0 application, shows that Asset structure has negative and significant effect on Capital structure, Sales growth has negative and significant effect on Capital structure, Profitability has negative but insignificant effect on Capital structure, Asset structure has negative but insignificant effect on Stock price, Sales growth has negative and significant effect on Stock price, Profitability has negative but insignificant effect on Stock price, Capital structure has positive but insignificant effect on Stock price. The result of indirect effect hypothesis test shows that asset structure has negative but insignificant effect on stock price through capital structure, sales growth has negative but insignificant effect on stock price through capital structure, and profitability has negative but insignificant effect on stock price through capital structure.